PJMHS 2021
DOI: 10.53350/pjmhs211561192
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Iron Deficiency Anemia in Hemodialysis patients at NIKD

Abstract: Background: Iron deficiency is a cause of anemia in many hemodialysis patients. It remains under diagnosed in patients with kidney diseas and it leads to inappropriate response to erythropoietin. Early diagnosis of this anemia before usage of erythropoietin is important, to prevent prescription of expensive erythropoietin and unnecessary costs to the patient and the health care system. This study was conducted to determine prevalence of iron deficiency anemia in hemodialysis patients. Methods: This study was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…The above results are consistent with previous research findings. [20] After receiving integrated IHBM nursing methods, MH patients’ subjective initiative has been significantly improved, and they have shifted from passive acceptance to active acceptance of knowledge related to hemodialysis. They have become more actively involved in self-care, thereby improving their behavior patterns and enhancing their self-care ability throughout the treatment process.…”
Section: Discussionmentioning
confidence: 99%
“…The above results are consistent with previous research findings. [20] After receiving integrated IHBM nursing methods, MH patients’ subjective initiative has been significantly improved, and they have shifted from passive acceptance to active acceptance of knowledge related to hemodialysis. They have become more actively involved in self-care, thereby improving their behavior patterns and enhancing their self-care ability throughout the treatment process.…”
Section: Discussionmentioning
confidence: 99%
“…Most of our study patients were on twice-per-week dialysis, depicting a significant association with anemia, which is also comparable with the published data by Sabir et al [ 20 ], in which twice-per-week dialysis was observed in 75% of study patients. The possible cause of anemia with the increased frequency of dialysis per week may be blood loss, which usually gets retained in the dialyzer machine [ 30 ]. Furthermore, our study results have represented the duration of hemodialysis and evaluated the association of anemia with every additional month in the duration of hemodialysis in ESRD patients.…”
Section: Discussionmentioning
confidence: 99%